Beginnings of interior environments - Jones, Lynn M.
Beginnings of Interior Environments, 11e, provides a practical approach to introductory interior design. The text addresses interior design holistically, stressing the importance of commercial and residential environments equally. Students are introduced to the history, design fundamentals, and building systems (construction, electrical, mechanical) of design through practical examinations and engaging discussions that encourage them to analyze the needs and desires of clients, and through the synthesis of this information, create healthful, safe, and sustainable environments that enhances their clients' quality of life.